Humanism in Inheritance Distribution in Sampang Madurese Culture - Afidah Wahyuni; Harisah Harisah (AHKAM : Jurnal Ilmu Syariah, 2019)
Critical issues in Islamic inheritance law in the modern context is mostly related to women’s proportion and position compared to men’s. Many believe that Islamic traditional inheritance law has patriarchal and misogynist characteristics. Therefore, the system is incompatible with the principle of gender equity and human rights. This paper aims at investigating the practice of inheritance distribution in Sampang Madura, and the humanism perspective of the system. This research relies on a qualitative approach by employing interviews, observation, and documentation. It is found that, in Sampang Madura, men and women have equal position in inheritance. The people of Sampang Madura combine the customary and Islam laws in their inheritance system. This study reveals that Madurese people do not marginalize women and uphold the value of humanism in the inheritance distribution by considering the implementation of maslahah principle.